Perceptions of nursing workloads and contributing factors, and their impact on implicit care rationing: A Queensland, Australia study. (17th September 2018) - Hegney, Desley Gail; Rees, Clare Samantha; Osseiran‐Moisson, Rebecca; Breen, Lauren; Eley, Robert; Windsor, Carol; Harvey, Clare
Abstract: Aims: To explore nurses' perceptions of factors affecting workloads and their impact on patient care. Background: Fiscal restraints and unpredictable patient illness trajectories challenge the provision of care. Cost containment affects the number of staff employed and the skill‐mix for care provision. While organisations may acknowledge explicit rationing of care, implicit rationing takes place at the point of service as nurses are forced to make decisions about what care they can provide. Method: A self‐report cross sectional study was conducted using an on‐line survey with 2, 397 nurses in Queensland, Australia. Results: Twenty to forty per cent reported being unable to provide care in the time available; having insufficient staff; and an inadequate skill‐mix. The respondents reported workload and skill‐mix issues leading to implicit care rationing. Over 60% believed that the processes to address workload issues were inadequate. Conclusions: Institutional influences on staffing levels and skill‐mix are resulting in implicit care rationing. Implications for Nurse Managers: Adequate staffing should be based on patient acuity and the skill‐mix required for safe care. Managers should be more assertive about adequate clinical workloads, involve staff in decision‐making, and adopt a systematic planning approach. Failure to do so results in implicit care rationing impacting on patient safety.